Child friendly app for spelling training - Sucena, Ana (2020)
Spelling skills are usually more difficult to acquire than reading skills. Nonetheless research based intervention proposals are scarce for spelling skills. In this study the impact of a child friendly spelling app on spelling skills is assessed. Results indicate an increase on spelling skills after training with the app.